A usable body: coaxing the body into and out of captivity at the museum. Issue 2 (3rd April 2019) - Autry, Robyn
Abstract : The visual logic of 'black' identity as a social and historical fact is presented at museums depicting the transformation of enslaved Africans to racial citizens. I focus on the work of the body in narrating this transition at a black history museum: the historical object on display – the captive African and later the US citizen – and the imagined visitor moving through the physical space of the museum. I consider the visual treatment of the enslaved body in captivity as broken, bowed, beaten and often nude in contrast to the post-abolition period when the body is positioned as erect, individuated, self-possessed and always clothed. I also discuss how the imagined visitor's body is oriented both to the narratives on display and to the built environment of the museum itself.